(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
During the excavations which took place in September 2011 in Nora di Pula inside the A1 post costantinian building , it was found the upper portion of a glass bottle. The finding may be considered exceptional for the partial integrity of the object, which contrasts with the fragmented nature of most of Nora glasses, and the reliability of the stratigraphic unit. The typological analysis has allowed to identify it as an Isings 50/51 b bottle, very common throughout the Roman world; but the lack of the lower part of the object and the consequent absence of the vitrarius mark, make it difficult to understand where it was made. The great diffusion of that kind of bottle, especially from the II century A.D., reflects the progressive achievement of typological and technological uniformity in its production.